Simulations du rapprochement des lieux de travail et de résidence et impacts sur le développement métropolitain en Île de France - Marie-Hélène Massot; Emre Korsu; Cyril Enault (Territoire en Mouvement)
Making the assumption that the multiplication of long-distance trips occurs as a consequence of greater difficulties encountered by households searching decent housing nearby workplaces, many experts argue that efficient urban policies promoting a diversified housing supply nearby job centres would allow more reasonable commuting distances and should go forth with a reduction in car traffic and a substainable urban development. On the basis of this diagnosis, the re-establishement of a greater balance on both quantitative and qualitative grounds, we present here a simulation model based on re-assignment of households closer to their workplaces and examine the potential of car traffic reduction in the case of the Paris region. We also identify the characteristics of reassigned households (especially social status, number of workers, family profile, residential location, job location, etc.). Third, we estimate the housing offer/demand imbalance after re-assignment (with specific interest for the case of housing for low-income groups).